Analisis Kinerja Keuangan Pada Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia (Periode 2019-2022) - Damanik, Christin Anggita; Hutapea, Herti Diana; Sihombing, Halomoan S (CV. ITTC INDONESIA, 2024)
This research aims to determine the financial performance of telecommunications companies listed on the Indonesia Stock Exchange (2019-2022 period). The sampling technique used in this research used a purposive sampling method, resulting in a sample of 9 telecommunications companies that met the research criteria. This research is quantitative research with the type of research being descriptive research. The data used is secondary data, the data collection method is documentation from financial reports published on the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The data analysis method uses a descriptive analysis method using ratio analysis. The data source used is secondary data. The results of the research show that if we look at the liquidity ratios contained in the current ratio, fast ratio, and cash ratio PT Centratama Telekomunikasi Indonesia has the best financial performance. If seen from the ratio of solvability which consists of ratio DER and DAR PT First Media has the best financial performance and for ratio LTDER PT Centratama Telekomunikasi Indonesia has the best financial performance. If seen from the ratio of activities which consist of the range of total asset turnover of PT Telkom Indonesia has the best financial performance and for the WCTR ratio PT Link Net has the best financial performance. Meanwhile, if we look at the results of profitability based on ROI, ROE, and ROA PT First Media has the best financial performance.